2015
DOI: 10.1021/acs.organomet.5b00558
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Characterization of Tantalum Alkyl Imides and Amide Imides. DFT Studies of Unusual α-SiMe3 Abstraction by an Amide Ligand

Abstract: Reaction of TaCl2(NSiMe3)­[N­(SiMe3)2] (1) with alkylating reagents form the alkyl amide imide complexes TaR2(NSiMe3)­[N­(SiMe3)2] (R = Me (2), CH2Ph (3)) and mixed amide imide compounds Ta­(NR′2)2(NSiMe3)­[N­(SiMe3)2] (R′ = Me (4), Et (5)). The reaction of 2 and 0.5 equiv of O2 leads to preferential oxygen insertion into one Ta–Me bond, yielding the alkoxy-bridged alkyl dimer Ta2(μ-OMe)2Me2(NSiMe3)2[N­(SiMe3)2]2 (6) as cis and trans isomers. Crystallization of the cis -6 and trans -6 mixture gave only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 91 publications
2
2
0
Order By: Relevance
“…The tantalum core adopts a pseudo-tetrahedral geometry (τ4 = 0.95) which is typical for 4coordinate d 0 Ta(V) complexes. 50,51 As expected, the Ta=Calkylidene bond length (1.90(1) Å) is significantly shorter than the Ta-Calkyl distances (2.14(1) and 2.156(1) Å), and falls in the expected range. 23,[36][37][38][39][40]52 The Rh centre adopts a square-planar coordination geometry (τ4 = 0.09) which is characteristic for 4-coordinate 16valency electrons Rh(I) species.…”
Section: Figuresupporting
confidence: 74%
“…The tantalum core adopts a pseudo-tetrahedral geometry (τ4 = 0.95) which is typical for 4coordinate d 0 Ta(V) complexes. 50,51 As expected, the Ta=Calkylidene bond length (1.90(1) Å) is significantly shorter than the Ta-Calkyl distances (2.14(1) and 2.156(1) Å), and falls in the expected range. 23,[36][37][38][39][40]52 The Rh centre adopts a square-planar coordination geometry (τ4 = 0.09) which is characteristic for 4-coordinate 16valency electrons Rh(I) species.…”
Section: Figuresupporting
confidence: 74%
“…This follows literature precedent for the reaction of [Y(N″)3] with n BuLi [30]. There is also a general lack of literature examples for benzyl ligands in the presence of silyl amide ligands indicating their incompatibility, with only examples of Sc, Ti, Al or Ta benzyls in the presence of N″,[36,[63][64][65] as well as Zr or Th benzyls with tris(silylamido)amines,[66,67] known.Reactions of [M(CH2Ph)] [M = Li(TMEDA), Na, K] with [Ce(TMP)3] in C6D6 were attempted. However, large amounts of solid material precipitated which we have been unable to characterise.…”
supporting
confidence: 62%
“…The 1:1 reaction of [Li(Ph)] with [Li(TMP)] in benzene at 80 °C for 2 hours afforded a brown suspension, wherein only some of the lithium phenyl was observed to dissolve. Upon cooling, pale yellow crystals suitable for X-ray diffraction studies were grown, which revealed this complex to be the hexanuclear (11) 18 (14), Li(1) 65 (10), N(1)-Li(2)-C (19) 124. 50 (11), N(1)-Li(2)-C(19A) 125.65 (10), C(19)-Li(2)-C(19A) 109.85 (9).…”
Section: Homometallic Speciesmentioning
confidence: 99%
“…13 shows the 1 H DOSY spectrum of (Ph . Similar approaches have also proved successful for tantalum [217] and could prove useful for studies of other coinage metals (copper [218] and silver [219]). American Chemical Society.…”
Section: External Calibration -Examples and Applicationsmentioning
confidence: 97%